Computers and computing information resources directory (Detroit Gale Research, 1987)
A descriptive guide to approximately 6,000 live anp print sources of information on general and specific applications of computers and data processing
Annual.
Keywords: Connors,Martin; Kroll, John; DeMaggio, Jannice A; Computers -- Bibliography -- Periodicals; Computer networks -- Directories; Computers -- Periodicals -- Directories; Electronic data processing consultants -- Directories; Electronic data processing -- Bibliography -- Periodicals; Information services -- Directories; Information storage and retrieval systems -- Directories; Research institutes -- Directories